COMMUNITY RIGHTS GUARANTEED BY LAW - DM, M. Yusuf; Sitinjak, Ronni Tunnas Mangapul; Gunawan, Hendra; Asmadi, Sofyan; Siswanto, Alen; Sinaga, Elga Gilbert Orion (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The rights of the people constitute a fundamental element of Indonesia's constitutional system and are directly guaranteed by the 1945 Constitution of the Republic of Indonesia as well as by statutory regulations derived from it. These guarantees encompass civil, political, economic, social, and cultural rights that must be respected, protected, and fulfilled by the state through clear, transparent, and accountable legal policies. This study aims to analyze the forms of legal guarantees for community rights, their implementation within the national legal framework, and the challenges encountered in achieving effective protection. The findings indicate that although the normative framework is comprehensively regulated, its practical implementation still faces various obstacles, such as regulatory inconsistencies, weak law enforcement, and low public awareness of their rights. Therefore, strengthening regulations, enhancing the capacity of state apparatus, and improving public education are essential to ensuring that community rights are fully and equitably realized.